The reproductive potential of Dwarf goats in the humid forest zone of Ashanti - Buadu, M.K. (1972)
The reproductive potential of Dwarf goats in the climatic conditions of the humid forest zone of Ashanti, Ghana was investigated. Data on incidence of multiple births, number of kids per birth and kidding intervals included.